1969
DOI: 10.1002/1097-0142(196908)24:2<355::aid-cncr2820240218>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Benign solitary schwannomas (neurilemomas)

Abstract: Three hundred and three patients with benign solitary neurilemomas, or schwannomas, not associated with the classical type of von Recklinghausen's disease were studied. One hundred and seventy‐two were women and 131 were men. Forty‐five percent of the tumors were seen in the extremities, and no specific area could be related to the development of these tumors. Approximately 9% of the tumors occurred in the soft tissues of the trunk and 14% in various unusual sites. Most patients were seen initially because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
273
0
21

Year Published

1974
1974
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 643 publications
(296 citation statements)
references
References 9 publications
2
273
0
21
Order By: Relevance
“…In a series of 303 cases reported by Das Gupta [10] and his associates only 16 cases where found to be in buccal mucosa and lip. In a study of 41 tumors Oberman [11] and Sulliger reported that 25% were located inside the mouth.…”
Section: Discussionmentioning
confidence: 96%
“…In a series of 303 cases reported by Das Gupta [10] and his associates only 16 cases where found to be in buccal mucosa and lip. In a study of 41 tumors Oberman [11] and Sulliger reported that 25% were located inside the mouth.…”
Section: Discussionmentioning
confidence: 96%
“…Malignant melanoma grows rapidly and has a poor prognosis, requiring adjuvant chemotherapy after surgical resection. 9 Das Gupta et al 10 reported 303 cases of solitary schwannoma, 19 of which had other malignancies and an increased risk of cancer. Because melanotic schwannoma has properties of schwannoma, malignancies in other areas must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The commonest cause was sebaceous cysts (34%), followed by thyroglossal cysts (13%), branchial remnants (9%) and dermoid 9% [10]. Approximately 10% of schwannoma are diagnosed in patients less than 21 years of age [2,3,9]. It is more commonly seen in adults.…”
Section: Case Reportmentioning
confidence: 99%